Overweight and Obesity are Associated with Poorer Survival Among Patients with Advanced Non-Small Cell Lung Cancer Receiving Platinum-Based Chemotherapy - Sutandyo N; Hanafi AR; Jayusman AM; Kurniawati SA; Hanif MA (International Journal of General Medicine, 2023)
Noorwati Sutandyo,1,2 Arif Riswahyudi Hanafi,3 Achmad Mulawarman Jayusman,3 Sri Agustini Kurniawati,1 Muhamad Alfin Hanif3 1Division of Hematology and Medical Oncology, Department of Internal Medicine, Dharmais National Cancer Hospital, Jakarta, Indonesia; 2Faculty of Medicine, Universitas Indonesia, Jakarta, Indonesia; 3Department of Pulmonology, Dharmais National Cancer Hospital, Jakarta, IndonesiaCorrespondence: Noorwati Sutandyo, Email noorwatis3@yahoo.comBackground and Aim: Most patients with non-small cell lung cancer (NSCLC) are diagnosed in advanced-stage disease and therefore have poor overall survival. It remains unclear whether nutritional status affects response rate and overall survival in NSCLC patients. This study aimed to evaluate the association of nutritional status with treatment response and overall survival in patients with advanced stage of NSCLC.Methods: Patients aged ≥ 18 years with stage II–IV NSCLC (January–June 2018) in a national cancer center in Indonesia were enrolled in this study. The patients were followed up for 2 years since NSCLC diagnosis was established. Clinical data including age, sex, histology of cancer, disease stage, cachexia, and weight status before chemotherapy were reviewed and analyzed. Logistic regression and Cox regression analyses were performed.Results: A total of 174 patients (71% males, mean age = 58± 9.4 years) was included. Complete response was found in < 1% patients, partial response 41%, stable disease 33%, and progressive disease 25%. Median survival was 12 months (95% CI: 11– 13 months). Mortality rate was 5.7 per 100 person-months. Poor survival was associated with being males (HR: 1.77, 95% CI: 1.15– 2.72, P = 0.009), and overweight or obesity (HR 1.67, 95% CI: 1.04– 2.69, P = 0.034). These associations were independent of sex, age, staging, histopathology, performance status and D-dimer level at baseline. Cachexia and BMI at baseline were not associated with treatment response.Conclusion: Males and having overweight or obesity are independently associated with lower survival in patients with advanced stage of NSCLC undergoing platinum-based chemotherapy.Keywords: body mass index, nutritional status, lung cancer